Shared mental representations underlie metaphorical sound concepts - Victor Rosi; Pablo Arias Sarah; Olivier Houix; Nicolas Misdariis; Patrick Susini (Scientific Reports, 2023)
Abstract Communication between sound and music experts is based on the shared understanding of a metaphorical vocabulary derived from other sensory modalities. Yet, the impact of sound expertise on the mental representation of these sound concepts remains blurry. To address this issue, we investigated the acoustic portraits of four metaphorical sound concepts (brightness, warmth, roundness, and roughness) in three groups of participants (sound engineers, conductors, and non-experts). Participants (N = 24) rated a corpus of orchestral instrument sounds (N = 520) using Best–Worst Scaling. With this data-driven method, we sorted the sound corpus for each concept and population. We compared the population ratings and ran machine learning algorithms to unveil the acoustic portraits of each concept. Overall, the results revealed that sound engineers were the most consistent. We found that roughness is widely shared while brightness is expertise dependent. The frequent use of brightness by expert populations suggests that its meaning got specified through sound expertise. As for roundness and warmth, it seems that the importance of pitch and noise in their acoustic definition is the key to distinguishing them. These results provide crucial information on the mental representations of a metaphorical vocabulary of sound and whether it is shared or refined by sound expertise.